Racial and Ethnic Differences in Mental Illness Stigma in California - Collins, Rebecca L. (RAND Corporation, 2014)
Report identifies racial and ethnic groups in California that are more likely to stigmatize those with mental illness, thereby helping understand who is at greatest risk of experiencing stigma within their own communities.